Evaluation of the Silicon Solar Cell Parameters - Kharchenko, V. (2019)
For estimation and prediction of PV solar cell parameters there was suggested and developed the methodology based on acceptance for consideration the important peculiarity internal photoeffect which mind-set in the fact that photon of sunlight can form only one electron-hole pair despite of its energy level and that the solar radiation is characterized by spectral distribution of photons of various length of a wave. The main point of the methodology is consideration the process of electron-hole pairs formation under influence of photons of given site of solar spectrum with semiconductor (silicon) used as solar cell substrate. Some results of this kind calculation are represented in the paper. Â© 2019, Springer Nature Switzerland AG.